Correction: Novel application of peptaibiotics derived from Trichoderma sp. for methanogenic suppression and enhanced power generation in microbial fuel cells. Issue 21 (28th February 2017) - Ray, S. Ghosh; Noori, Md. T.; Ghangrekar, M. M.
Abstract : Correction for 'Novel application of peptaibiotics derived from Trichoderma sp. for methanogenic suppression and enhanced power generation in microbial fuel cells' by M. M. Ghangrekar et al., RSC Adv., 2017, 7, 10707–10717.